The thesis statement in translations of academic discourse: an exploratory study - Pisanski Peterlin, Agnes (The Journal of Specialised Translation, 2008)
Research has shown that languages exhibit substantial differences in the conventions of academic discourse. The thesis statement has been identified as one of the conventions in which differences between languages have been observed. This paper analyses thesis-statement use and form in a corpus of 90 geography research articles: Slovene originals, their English translations, and English originals are compared in terms of thesis-statement use and form. The results show that the thesis statement is used more frequently in original English research articles than in original Slovene research articles, and that the English translations of the latter correspond to the Slovene originals. The results also reveal differences between the two sets of originals in terms of thesis-statement position and the degree of authorial presence, again with the English translations corresponding to the Slovene originals. A comparison of the Slovene originals and their English translations identifies certain changes made during translation. The findings of this study suggest that the differences in thesis-statement use and form between the two languages could create problems in translation.